Evaluation of Human β-defensin-3 Diagnostic Role in a Group of Iraqi Patients with Osteoporosis - Zahraa S. Hassan; Layla O. Farhan (مجلة كلية الطب)
Background: Osteoporosis (OP) is a prevalent age-related condition that increases the risk of fracture and bone fragility, as result loss of bone mass as well as micro-architectural degradation of the bone, thereby reducing the mass and strength of bone. Human β-defensin (HBD-3) is ananti-inflammatory peptide andcrucial part of the human innate immune system. Giving early therapeutic intervention for OP requires an early diagnosis.